Patterns of Federated Identity Management Systems as Architectural Reconfigurations - Nizamani, Hyder; Tuosto, Emilio (Electronic Communications of the EASST, 2011)
This paper proposes a formal model of Federated Identity Management systems (FIMs) in terms of architectural design rewriting. FIMs allow cross-domain user authentication to enable access control across the organisations under the concept known as Circle of Trust (CoT). Patterns of FIMs emerged as recurring CoT scenarios due to the fact that each of the pattern has different security and trust requirements. This paper proposes a formal model for FIMs to characterise their patterns as architectural styles. More precisely, an architectural style is given to precisely pinpoint all possible legal configurations of the CoT in terms of the patterns. The proposed model is specified through style-consistent (graphical) designs in terms of architectural design rewriting (ADR).